Estrategias didácticas para fortalecer el aprendizaje de Lengua Literatura en séptimo grado, Escuela de Educación General Básica ¨Teniente Hugo Ortiz¨, 2024-2025 - Muñoz Bravo, Susana Belén (2025)
The research work Teaching strategies to strengthen the learning of Language and Literature in the seventh grade of the Teniente Hugo Ortiz Basic General Education School, period 2024- 2025, which aims to determine the impact of teaching strategies on the learning of Language and Literature in the seventh grade, is a descriptive research, with a mixed approach and nonexperimental design. The theoretical framework addresses updated topics on teaching strategies and Language and Literature. The population investigated includes 30 students and one teacher. The information was collected through an interview with the teacher and an evaluation of the students. The results of the research reflect that a considerable number of students are close to achieving the required learning in Language and Literature, a situation that requires an innovative pedagogical intervention to ensure that all students develop their maximum potential. To this end, the teaching strategies that contribute to the learning of Language and Literature were determined and the alternative guideline “Teaching strategies: a creative way of learning” was designed. It consists of 15 activities that have as their main input teaching strategies exclusive to Language and Literature. It is expected that its application will contribute significantly to strengthening the learning of this important subject